2022
DOI: 10.3389/fmicb.2022.1010387
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of plasmid and tet(X4) in an Escherichia coli isolate coharboring blaNDM-5 and mcr-1 after acquiring an IncFII tet(X4)-positive plasmid

Abstract: The prevalence of plasmid-mediated tigecycline resistance gene tet(X4) is presenting an increasing trend. Once tet(X4)-bearing plasmids are captured by multidrug-resistant bacteria, such as blaNDM and mcr-coharboring bacteria, it will promote bacteria to develop an ultra-broad resistance spectrum, limiting clinical treatment options. However, little is known about the destiny of such bacteria or how they will evolve in the future. Herein, we constructed a multidrug-resistant bacteria coharboring tet(X4), blaND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The previous studies also reported that tetA was dominantly detected in pig feces (44.9% [43] and 94.7% [44]), pig farm waste (66.7% [45]), pig slaughterhouse wastewater (50% [37]), and the environment (88.9% [44] and 100% [45]). Plasmidmediated tetX (variant tetX4) was detected in E. coli from samples of pig feces (31.03%), pig anal swabs (37.93%), farm environments such as water (6.89%), soil (6.89%) [46], dust (0.9%) [47], and pig slaughterhouses [48]. According to Jia et al [27], tetX exhibited a high relative abundance in pig farm wastewater of 106.3 copies/16S rRNA gene copies.…”
Section: Detection Of Tetracycline Resistance Genesmentioning
confidence: 99%
“…The previous studies also reported that tetA was dominantly detected in pig feces (44.9% [43] and 94.7% [44]), pig farm waste (66.7% [45]), pig slaughterhouse wastewater (50% [37]), and the environment (88.9% [44] and 100% [45]). Plasmidmediated tetX (variant tetX4) was detected in E. coli from samples of pig feces (31.03%), pig anal swabs (37.93%), farm environments such as water (6.89%), soil (6.89%) [46], dust (0.9%) [47], and pig slaughterhouses [48]. According to Jia et al [27], tetX exhibited a high relative abundance in pig farm wastewater of 106.3 copies/16S rRNA gene copies.…”
Section: Detection Of Tetracycline Resistance Genesmentioning
confidence: 99%
“…Plasmids, such as IncFII, IncFIB, IncFIA, IncX1, IncQ1, IncA/C, IncHI1, and others, have been discovered to be the key carriers for propagating tet (X4) 14 , 15 . Tigecycline resistance in K. pneumoniae is mainly caused by mutations in the genes ramR , soxR , oqxR , rpsJ , and tet (A).…”
Section: Introductionmentioning
confidence: 99%